Population Structure, Regeneration Status, and Threats to Dobera glabra (Forssk.) Poir. in Chifra District, Afar Regional State, Ethiopia - Kflay Gebrehiwot; Ali Zeynu (International Journal of Forestry Research)
Dobera glabra is a much branched multipurpose evergreen shrub or tree, which is distributed in Acacia savanna, Acacia open woodland with grassy clearings, and Acacia nubica scrub. This study investigates the population structure, regeneration status, cultural importance, and major threats to D. glabra and provides input for policy and decision-makers to develop conservation strategies that improve the population of the species. A sample plot of 30 × 20 meters and 10× 10 meters were systematically laid along transect lines for the mature D. glabra population and seedling and saplings of the species, respectively. The historical distribution and principal threats to D. glabra were collected through semistructured interviews and focused group discussion with the purposively selected informants. Moreover, direct field observation of threats such as cutting and debarking was recorded. The density of D. glabra was found to be 18.33 stem ha−1. The mean DBH was 43.55 cm (SE ± 1.58), showing a bell-shaped pattern implying the mid-DBH class is the dominant class. The mean height and crown diameter was 5.5 m (SE± 0.19) and 8.60 m (SE± 0.31), respectively. Furthermore, the regeneration status of the D. glabra was found to be extremely poor. The major threats to the species were identified as drought, lightning, grazing, cutting, and windfall. The population structure of the species revealed a bell-shaped pattern. The extremely poor natural regeneration status of the species shows the need to implement a reactive conservation approach.